Crystallization process and chemical disorder in flash evaporated amorphous gallium antimonide films - Dias Da Silva, J. H. [UNESP]; Cisneros, J. I. [UNESP]; Cardoso, L. P. [UNESP] (My University, 1994)
In this work we describe a flash evaporation system specially built to produce amorphous films of III-V compounds and characterize GaSb films using optical, electrical and X-Ray diffraction measurements. Changes in the composition of the GaSb samples were obtained by the use of different crucible temperatures. In such samples, consequently, the optical absorption edge and the DC electrical conductivity were modified. The departure from stoichiometry in GaSb films is analyzed on the basis of these results which can be used as an evidence of the chemical disorder. This kind of disorder is represented by either wrong bonds or sites with different coordination. Thermal annealing with a sequence of increasing temperatures first induced detectable variations in the optical absorption edge and in the vibrational properties of the amorphous GaSb. These variations are compatible with the GaSb local ordering and were observed by Raman scattering and infrared absorption spectra. The annealing at higher temperatures allowed the crystallization of the material confirmed by X-Ray diffraction. From these experimental results a crystallization mechanism based on the segregation of Sb excess coming from the crystallized regions toward the amorphous tissue is proposed.